Vulnerability to Ideologically-Motivated Violence Among Individuals With Autism Spectrum Disorder - Woodbury-Smith, Marc R.; Loftin, Rachel; Westphal, Alexander; Volkmar, Fred R. (Frontiers in Psychiatry, 2022)
People with autism spectrum disorder (ASD) are represented among those who espouse extremist thought and have committed violent acts associated with their beliefs. Media often highlight a perpetrator’s psychiatric diagnosis following acts of mass violence, which in some instances has included ASD. ASD may itself not provide useful information for understanding motivations. Instead, understanding specific traits and neuropsychological and other vulnerabilities may offer an opportunity to make sense of these very complex events.